2013
DOI: 10.1074/jbc.m113.520791
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase M Is a Positive Allosteric Modulator of the Kinin B1 Receptor

Abstract: Background: Carboxypeptidase M (CPM) generates agonist for the kinin B1 receptor (B1R). Results: CPM binds to B1R on the cell membrane and allosterically increases B1R agonist affinity. Conclusion: CPM is a positive allosteric modulator of the B1R, thereby increasing receptor signaling. Significance: Interfering with CPM binding to B1R could be a novel approach to inhibit deleterious effects of B1R signaling in inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 72 publications
0
17
0
1
Order By: Relevance
“…These included CPM, which has a potential role in cell signaling and tissue remodeling [43][44][45]; MME, a stroma-specific protein used in determining the pathologic diagnosis of endometrial stromal sarcoma as opposed to other sarcoma [46][47][48]; and ENPP3, in which we noted strong uterine expression in the Human Protein Atlas resource [49][50][51]. Ectonucleotide pyrophosphatase/phosphodiesterase 3, a member of a family of proteins with ATPase activity involved in the hydrolysis of extracellular nucleotides, is a transmembrane protein classed with other cell-surface ectoATPases that modulate complex interactions with nucleotides and their breakdown products [52][53][54].…”
Section: Proteomics Of the Premenopausal Endometriummentioning
confidence: 99%
“…These included CPM, which has a potential role in cell signaling and tissue remodeling [43][44][45]; MME, a stroma-specific protein used in determining the pathologic diagnosis of endometrial stromal sarcoma as opposed to other sarcoma [46][47][48]; and ENPP3, in which we noted strong uterine expression in the Human Protein Atlas resource [49][50][51]. Ectonucleotide pyrophosphatase/phosphodiesterase 3, a member of a family of proteins with ATPase activity involved in the hydrolysis of extracellular nucleotides, is a transmembrane protein classed with other cell-surface ectoATPases that modulate complex interactions with nucleotides and their breakdown products [52][53][54].…”
Section: Proteomics Of the Premenopausal Endometriummentioning
confidence: 99%
“…CPM is a largely distributed enzyme that cleaves C-terminal lysine or arginine from other peptides and proteins, including anaphylatoxins, chemokines, enkephalins and growth factors (Deiteren et al, 2009 ) that may question its specificity as a pharmacological target. While the regulatory role of CPM in kinins and B1R activity has been fairly well documented (Erdos and Sloane, 1962 ; Zhang et al, 2013a , b ; Couture et al, 2014 ; Regoli and Gobeil, 2015 ), the impact of CPM on the physiological functions of other endogenous substrates, and particularly in insulin resistance, is still unknown and remains to be studied. In the present study, the inhibition of B1R-agonists formation by Mergetpa has not been directly demonstrated and is not an easy task in vivo due to the short life of these peptides, but the impact of CPM blockade is in accordance with the beneficial effects of B1R antagonism in insulin resistance and its associated oxidative stress and inflammatory mechanisms (Dias et al, 2010 ; Dias and Couture, 2012b ; Haddad and Couture, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to generating B1R agonists in close proximity to the receptor, biochemical studies in transfected cells suggest that CPM interacts with the B1R to enhance B1R signaling. Kinin (BK or kallidin) binding to the CPM active site causes a conformational activation of the B1R (Zhang et al, 2013a ) and basal binding of CPM to extracellular loop 2 of the B1R results in positive allosteric modulation of B1R signaling to its orthosteric agonist (Zhang et al, 2013b ). Recently, CPM and B1R were found upregulated along with the inducible nitric oxide synthase (iNOS) and interleukin-1β (IL-1β) in aorta, renal cortex and liver in a rat model of insulin resistance induced by high glucose feeding (Haddad and Couture, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our studies have identified a critical complex in lipid raft microdomains between kB1R and CPM, the enzyme that generates its agonist (8, 9). This kB1R/CPM heterodimer facilitates kB1R signaling in three ways (8, 9, 64, 65): 1) Basal CPM binding allosterically enhances kB1R affinity for agonist; 2) Kinin substrate (i.e., BK or KD) binding to CPM’s active site causes a conformational change that is transmitted via protein-protein interaction to activate the kB1R without agonist. 3) CPM cleaves the C-terminal Arg of KD (or BK) to generate kB1R agonist that further activates kB1R.…”
Section: Discussionmentioning
confidence: 99%